2017
DOI: 10.1016/j.fertnstert.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone agonist trigger increases the number of oocytes and embryos available for cryopreservation in cancer patients undergoing ovarian stimulation for fertility preservation

Abstract: Utilization of a GnRH-agonist trigger increases the number of MII oocytes and 2PN embryos available for cryopreservation in cancer patients undergoing COS for fertility preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…This syndrome could not only result in a delay in cancer treatment but also amplify the baseline risk for coagulopathy and other cancer-related morbidities ( Turan et al ., 2013 ; Kim et al ., 2015 ; Oktay et al ., 2010 ). Besides this, GnRH agonist trigger usually results in a greater mature (MII) oocyte yield without a reduction in clinical pregnancy or live birth rates in cryopreservation cycles ( Rodriguez-Wallberg & Oktay, 2010 ; Rodgers et al ., 2017 ; Oktay et al ., 2010; Pereira et al ., 2017 ). The most recent studies showed no differences between these two protocols concerning number of retrieved oocytes ( Turan et al ., 2013 ; Kim et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome could not only result in a delay in cancer treatment but also amplify the baseline risk for coagulopathy and other cancer-related morbidities ( Turan et al ., 2013 ; Kim et al ., 2015 ; Oktay et al ., 2010 ). Besides this, GnRH agonist trigger usually results in a greater mature (MII) oocyte yield without a reduction in clinical pregnancy or live birth rates in cryopreservation cycles ( Rodriguez-Wallberg & Oktay, 2010 ; Rodgers et al ., 2017 ; Oktay et al ., 2010; Pereira et al ., 2017 ). The most recent studies showed no differences between these two protocols concerning number of retrieved oocytes ( Turan et al ., 2013 ; Kim et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the elicited flare of LH as well as FSH resembles the natural midcycle surge of gonadotrophins and was found to effectively stimulate final oocyte maturation and ovulation (10), leading to the development of competent embryos as recently demonstrated in PGT-A cycles (11). Moreover, studies in oocyte donors (12) and oncologic fertility-preservation patients (13,14) demonstrated a significant increase in MII oocytes and the number of good-quality embryos in GnRHa-triggered cycles as compared with hCGtriggered cycles. Nonetheless, it is worth noticing that others have not corroborated these findings (15)(16)(17).…”
Section: Gnrha Trigger-improving Oocyte Yield and Embryo Competence?mentioning
confidence: 92%
“…The same group in an extended analysis (13), including 129 breast cancer patients (46 in the GnRHa trigger group versus 83 in the hCG trigger group), confirmed their previous results in terms of more MII oocytes (77.3% versus 67.6%, p ¼ 0.007) and a higher number of cryopreserved embryos (7.7 versus 5.4, p ¼ 0.002) in the GnRHa trigger group. More recently, a larger retrospective cohort study (14) included 341 patient who underwent oocyte freezing for fertility preservation (75.3% breast cancer patients) and reported a higher number of MII oocytes and embryos cryopreserved (11.8 versus 9.9, p ¼ 0.04; and 9.2 versus 6.4, p < 0.001) after GnRHa trigger.…”
Section: Fertility Preservation In Cancer Patientsmentioning
confidence: 99%
“…The LBR using GnRHa-triggered cycles is comparable to hCG-triggered cycles provided that a modified luteal phase support is applied [79][80][81]. Importantly, it was shown that the number of MII oocytes and embryos were significantly higher after a GnRHa trigger as compared to an hCG trigger [82][83][84]. The finding was supported by a recent systematic review and meta-analysis in which two RCTs showed a significant increase in the number of good quality embryos after a GnRHa trigger compared to an hCG trigger (MD 0.94, 95% CI 0.01-1.87) [85].…”
Section: Ovulation Triggermentioning
confidence: 96%